ANTIMICROBIAL POTENTIAL OF HERBAL AND CHEMICAL NEONATAL EYE DROPS - Thakur, Nitika; Kumari, Jyoti; Sharma, Monu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study focuses on exploring the antimicrobial potential of chemical (Tobastar and natamycin) and herbal eye drops (Itone) which are specifically preferred against neonatal eye infections. Methods: Well diffusion method (for testing the antimicrobial potential of selected eye drops against different bacterial and fungal strains), minimum inhibitory concentration (MIC) (broth dilution method) for detecting the MIC effective against various strains taken into consideration. Results: The results indicated that Itone and Tobastar are effective against bacterial strains, thus highlighting the importance of these two eye drops against bacterial infections, whereas natamycin is effective against fungal infection. Conclusion: It may be concluded that the herbal eye drop (Itone) and the chemical eye drop (Tobastar) are effective against bacterial infections. The components such as neem, tulsi, kapur, and honey in herbal composition possess good antibacterial activity confirming the great potential of bioactive compounds and are useful for the growth inhibition of the carcinogenic bacterium. The alkaloids, flavonoids and saponins are based on antibiotic principles and are actually the defensive mechanisms of the plant against pathogens and chemical eye drop, that is, natamycin is effective against fungal infections, which may be due to the presence of polyene antifungal agent which works against fungal infections. There is a need to optimize the blending of the different herbal and chemical components to form a single effective antimicrobial formulation (more of herbal component and less chemical components) against neonatal infections.